Minocycline treatment reduces white matter damage after excitotoxic striatal injury - Guimarães, Joanilson S. (2010)
We investigated the protective effects of minocycline following white matter damage (WMD) in the rat striatum. Excitotoxic lesions were induced by N-Methyl-D-Aspartate (NMDA) microinjections and caused striatal damage, concomitant with microglial/ macrophage activation. The excitotoxic lesion both damaged oligodendrocytes (Tau-1+ cells) and caused a decrease in tissue reactivity for myelin basic protein (MBP) after postlesional day 3 (PLD). Treatment with the semi-synthetic tetracycline antibiotic minocycline, however, led to oligodendrocyte preservation and decreased myelin impairment. Taken together, these results suggest that white matter damage (WMD) is an important component of the physiopathology of acute striatal damage and that microglial/ macrophage activation contributes to this pathological phenomenon.